The Quranic term between Truth and metaphor (Journal of the College of Basic Education, 2022)
The Qur’anic text is the highest text in eloquence, and the eloquent have challenged them to come up with the same, even if it waseach other at noon. The metaphorical meanings abounded in the Qur’anic text, so much so that it was said that the metaphor is multipliedSpeech has become a reality, and for this reason a number of scholars, including Ibn Al-Atheer, counted the entire Qur’an as a reality without metaphor.This research targets the metaphorical and real meanings in a number of Quranic vocabulary, such as(The sky), And the (mercy)The sky is its true meaning: all that is above you, which is space, the roof of the house, and its meaningMetaphorical: rain and mercy, its real meaning: kindness and tenderness, while its metaphorical meaning is paradise.Introduction :The Holy Qur’an is the dear book of God, the constitution of Islam and its tolerant law.